XX Stoletie: Natsional'naya sbornaya po lyzhnym gonkam - "komanda veka" - Ramenskaya, T. I. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this paper was the appreciation the achievement of Russian skiers in XX century. The author gives the comparative analysis of the results of Russian and foreign athletes. She mentions everyone, who related to the "Team of the Century" and has made that team such excellent. The training of the "Team of the Century" was carried out in cooperation and by the joint work of chiefs of federation, coaches, doctors, masseurs, scientists, who managed jeweler work for direct leading of each athlete to the main start.